Q: 9x plus 12 divided by 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3 / 9x+63 / 3(3x+2)1 / 3x+2

(x - 3x - 6) / 6 = (3x + 2) / 3 ∴3x - 9x - 18 = 18x + 12 ∴3x - 9x - 18x = 12 - 18 ∴-24x = -6 ∴ x = 1/4

-9x-25=3 -9x=28 9x=-28 x=-28/9

-10x+3 = -x+12 -10x+x = 12-3 -9x = 9 x = -1

- 7x + (9x - 3) = - 7x + 9x - 3 = 2x - 3

Related questions

If: 12 = 9x+3 Then: 12-3 = 9x And: 9 = 9x So: x =1

Dividend: x3+4x2-9x-36 Divisor: x+3 Quotient: x2+x-12

3 / 9x+63 / 3(3x+2)1 / 3x+2

(x - 3x - 6) / 6 = (3x + 2) / 3 ∴3x - 9x - 18 = 18x + 12 ∴3x - 9x - 18x = 12 - 18 ∴-24x = -6 ∴ x = 1/4

-9x-25=3 -9x=28 9x=-28 x=-28/9

no

-10x+3 = -x+12 -10x+x = 12-3 -9x = 9 x = -1

- 7x + (9x - 3) = - 7x + 9x - 3 = 2x - 3

9x + 8 = 6x + 20(- 8 from both sides)9x = 6x + 12(- 6x from both sides)3x = 12(divide both sides by 3)x = 4

9x + 5 = 5x + 179x + 5 - 5x = 179x - 5x = 4x5-4x=1717-5=1212 divided by 4 = 3x=3

(x + 12)(x - 3)

x+5+3x-7+9x+3-4x Collect like terms: 9x+1